2010
DOI: 10.1590/s0001-37652010000300017
|View full text |Cite
|
Sign up to set email alerts
|

OSL age determinations of Pleistocene fluvial deposits in Central Amazonia

Abstract: Absolute dating methods have been used in chronological studies of geological processes and sedimentary units of Quaternary age in Central Amazonia, Brazil. Although radiocarbon dating has been very useful in archaeological research and soil studies, the temporal interval of this method is inefficient in evaluating the sedimentation aspects and geological events from the beginning of the Quaternary in the Amazon basin. The use of crystal luminescence dating has been one of the most promising tool for determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 29 publications
1
42
0
24
Order By: Relevance
“…The palaeogeographic mechanism for this vicariance event apparently involved the establishment of the current course of the lower Negro River in response to a series of neotectonic faulting events [10,47,48] (see electronic supplementary material). Supporting this molecular dating result, Soares et al [47] found evidence for an age of about 0.4 Ma for the initiation of sedimentation covering the Miocene Novo Remanso formation along the lower Negro River.…”
Section: Discussion (A) Testing the Refuge Hypothesismentioning
confidence: 99%
“…The palaeogeographic mechanism for this vicariance event apparently involved the establishment of the current course of the lower Negro River in response to a series of neotectonic faulting events [10,47,48] (see electronic supplementary material). Supporting this molecular dating result, Soares et al [47] found evidence for an age of about 0.4 Ma for the initiation of sedimentation covering the Miocene Novo Remanso formation along the lower Negro River.…”
Section: Discussion (A) Testing the Refuge Hypothesismentioning
confidence: 99%
“…Middle Miocene strata, dated in Central Amazon outcrops, in the vicinity of Manaus, was informally designated as Novo Remanso Formation (Rozo 2004, Rozo et al 2005, Dino 2006a, b, Soares 2007, Soares et al 2010a,b, Dino et al 2012, on the assumption that Alter do Chão Formation was as old as the Cretaceous, justifying a new Cenozoic stratigraphic unit in the basin. This Cenozoic unit supports the high relief of the regions of Manacapuru, Manaus, Itacoatiara, Itapiranga and São Sebastião do Uatumã localities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since several glacial and interglacial stages occurred, with consequent droppings and risings of sea level, several differently-aged fluvial terraces were built up along the rivers of Brazilian Amazon and other neighboring countries (Franzinelli & Ori 1988, Rossetti et al 2005, Gonçalves Junior 2013, Carlotto et al 2008, Soares et al 2010a). In the Central Amazon area, the oldest terrace is probably represented by the Içá Formation, other known, ancient fluvial terraces of the Solimões River, informally denominated as Upper Terrace, present ages of approximately 200,000 years Before Present (BP) and are continuous and parallel to the major rivers (Soares et al 2010a, b, Gonçalves 2013, being only interrupted by tributaries like the Purus and Madeira rivers. During the Pleistocene, occurred new extinction processes because of the environmental changes deriving from several droppings and risings of sea level.…”
Section: Amazon Rivermentioning
confidence: 99%
“…A coesão é aumentada pela granulação mais fina dos sedimentos, que tornam os bancos mais coesos (Ikeda, 1989;Törnqvist, 1993), conforme verificado nas camadas de lama (silte e argila) que compõem a estratificação heterolítica inclinada das ilhas e barras marginais desse sistema fluvial. Além disso, a maioria das ilhas é vegetada (inclusive por vegetação de médio a grande porte) e apresenta tempo de fixação entre 1.300 e 7.500 anos AP, de acordo com dados de datação por luminescência de cristais e radiocarbono obtidos nos estudos de Sternberg (1960), Absy (1979), Soares (2007), Soares et al (2010) e Rozo et al (2012.…”
Section: Resultados E Discussõesunclassified
“…Estudos geológicos detalhados na região entre Manacapuru-Manaus-Autazes, Amazônia Central (Soares, 2007;Soares et al, 2010;Gonçalves Júnior, 2013), permitiram definir sobre as unidades do Cretáceo-Mioceno (formações Alter do Chão e Novo Remanso) três níveis de terraços fluviais quaternários, constituídos principalmente de areia e lama (argila e silte), com estratificação heterolítica inclinada, que apresentam idade entre 240.000 e 1.300 anos AP. Os terraços estão dispostos em faixas paralelas às margens do sistema fluvial Solimões-Amazonas e são contínuos por dezenas de quilômetros.…”
Section: Contexto Geológicounclassified